The sinonasal bacterial microbiome in health and disease. Issue 1 (February 2016) - Ramakrishnan, Vijay R.; Hauser, Leah J.; Frank, Daniel N.
Abstract : Purpose of review: The development of culture-independent bacterial DNA sequencing techniques and integration into research practice has led to a burgeoning interest in the microbiome and its relevance to human health and disease. Introduction into the study of chronic rhinosinusitis in the past few years has shaped current thinking on the role of bacteria in the disease process. Recent findings: Rich and diverse populations of bacteria inhabit the sinonasal cavity at all times. Decreased bacterial richness and diversity may be associated with disease state and outcomes. Summary: Although there is much to be explored, the sinus microbiome appears to have potentially promising roles in many aspects of sinus health and disease.